2022
DOI: 10.1073/pnas.2207037119
|View full text |Cite|
|
Sign up to set email alerts
|

Archaeal bundling pili of Pyrobaculum calidifontis reveal similarities between archaeal and bacterial biofilms

Abstract: While biofilms formed by bacteria have received great attention due to their importance in pathogenesis, much less research has been focused on the biofilms formed by archaea. It has been known that extracellular filaments in archaea, such as type IV pili, hami, and cannulae, play a part in the formation of archaeal biofilms. We have used cryo-electron microscopy to determine the atomic structure of a previously uncharacterized class of archaeal surface filaments from hyperthermophilic Pyrobaculum … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 93 publications
0
19
0
Order By: Relevance
“…Further studies into the TasA/TapA system will be needed to understand in detail the mechanisms of assembly of TasA fibres compared to Gram-negative pili, which employ Chaperone-Usher systems or proteolytic cleavage for assembly 30 , 31 . Interestingly, very recent studies have demonstrated that fibres in extremophile archaea also are donor-strand-complemented 38 , 39 , with some archaeal systems even structurally related to TasA 39 , which suggests that donor-strand assembly is a ubiquitous strategy for the assembly of highly stable fibres.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further studies into the TasA/TapA system will be needed to understand in detail the mechanisms of assembly of TasA fibres compared to Gram-negative pili, which employ Chaperone-Usher systems or proteolytic cleavage for assembly 30 , 31 . Interestingly, very recent studies have demonstrated that fibres in extremophile archaea also are donor-strand-complemented 38 , 39 , with some archaeal systems even structurally related to TasA 39 , which suggests that donor-strand assembly is a ubiquitous strategy for the assembly of highly stable fibres.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, our experiments show the importance of a loop (containing residues 174–177) extending away from the fibre surface in mediating these interactions. Interestingly, in a recent study on a TasA-like system (archaeal bundling pili (ABP)) in hyperthermophilic archaea 39 , fibres formed ordered, six-fibre bundles. We detected bundles of variable sizes for TasA, which also appear more flexible.…”
Section: Discussionmentioning
confidence: 99%
“…ThT-stainable fibrils were investigated by solid-state NMR ( 10 ), and in parallel to this study nonamyloid filaments by cryo-EM ( 18 ) were studied at a resolution of 3.5 Å. Furthermore, a structural relationship between archaeal and bacterial biofilms was suggested on the basis of a 4.0 Å cryo-EM structure of Pyrobaculum calidifontis bundling pili ( 19 ).…”
mentioning
confidence: 99%
“…We have previously shown that Pyrobaculum calidifontis , a hyperthermophilic archaeon of the order Thermoproteales 40 , which lacks both Ced and Ups systems, is prone to aggregation mediated by bundling pili related to TasA-like fibers, a major component of the biofilm matrix in many bacteria 41 . We thus explored whether P. calidifontis cells produce pili which could be involved in DNA transfer.…”
Section: Resultsmentioning
confidence: 99%